Hubungan Antara Pengetahuan dan Sikap Petani terhadap Tindakan Petani Dalam Penggunaan Alat Pelindung Diri (Studi Kasus: Desa Ayunan, Kecamatan Abiansemal, Kabupaten Badung) - RESTHA, PAMELA ALDA; ASTITI, NI WAYAN SRI; PARINING, NYOMAN (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
The Correlation between Farmer’s Knowledge and Attitudes towards Their Behavior in the Use of Personal Protective Equipment (Case study in Ayunan Village, Abiansemal District, Badung Regency) The study employs an analytical survey by employing cross sectional approach in order to investigate and to describe the correlation between farmer’s knowledge and attitudes towards their behavior in the use of spray pesticide personal protective equipment in Ayunan Village, Abiansemal District, Badung Regency by the year of 2020. There are 334 farmers who become members of Subak in Ayunan Village, used as population of the study. The number of research samples is 35 farmers. The data is analyzed by using chi square test. The study employs a simple random sampling with a questionnaire as the instrument. According to the results of the Product Moment Correlation test, the significance value of the pearson correlation of respondents' knowledge is 0.000 < 0.05. It can be concluded that there is a correlation between farmer’s knowledge and behavior in the use of PPE. In the attitude variable, the significance value of the pearson correlation is 0.000 < 0.05, so it can be concluded that there is a correlation between attitudes and behavior of farmers in the use of PPE.